(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
This study set out to investigate the relationship between housing finance and sustainable housing development in Nigeria. The study adopted the Geographically Weighted Regression (GWR) methodology and the panel fixed effect model to study housing finance, and sustainable housing development in a bid to explore their implications for urbanisation in Nigeria. Geographically weighted regression (GWR) is an exploratory technique mainly intended to indicate where non-stationarity is taking place on the map, that is, where locally weighted regression coefficients move away from their global values. Results suggests that housing finance has a positive and significant effect on sustainable housing availability in Nigeria. Results also suggest that housing development has positive significant impact on urbanisation in Nigeria. The study concludes that housing finance is indispensable in the pursuit of decent urbanisation and should be shored-up at all quarters in order to help control the housing deficits in Nigeria. The study recommends that Governments at all levels and its agencies should strive harder to increase public capital spending in a bid to provide more infrastructure and housing for the populace since it was shown by this study’s finding to have positive significant impact on sustainable housing development in Nigeria.